Mistura de fungicidas sistêmicos com cúpricos e análise espaço temporal de doenças do cafeeiro - Paula, Paulo Victor Augusto Azevedo de (2018)
The brown eye spot and rust are the main diseases of coffee, causing defoliation and, consequently, lower productivity and loss of beverage quality. Moreover, soil fertility is directly correlated with the emergence of these diseases and the equilibrium of soil bases such as Ca, Mg, and K may predispose plants to fungal infection. In addition, chemical control is used to control diseases in the field. Thus, two experiments were carried out in the field to verify the epidemiology and form of control for rust and brown eye spot in leaves and fruits using soil fertility and chemical control. In the first experiment, the objective was to evaluate the temporal progress of the disease and its relationship with plant nutrition and soil fertility in drip irrigated crops using geostatistics. The incidence of the disease was evaluated in 100 fruits in the middle third of five plants / sampling point, performed 30 days before harvest and at harvest dates: April 20 and May 20, 2015, totaling two evaluations. This interval was necessary to verify the distribution of the disease over time. Soil productivity and soil fertility were also evaluated at each point annually. The incidence of the disease in the sampled sites was plotted and the semivariograms models were adjusted and the data interpolated by ordinary kriging, thus constructing the maps of the disease, production and soil fertility for the macronutrients % Mg, % K, Ca / Mg, and Ca / K. In the regions with higher incidence, the higher participation of Mg and K in the CEC pH 7 of the soil was observed, especially when the Ca / Mg and Ca / K ratios decreased, which made Ca unavailable to the plant. The areas with lower productivity had a higher incidence of the disease. The incidence of brown eye spot in coffee fruits in drip irrigation ranged from 0 to 17% between April and May 2015. There was a variation in the incidence of the disease throughout space, with spatial dependence and the presence of foci. The second experiment aimed to evaluate the control of these diseases with systemic fungicide associated or not with copper-based protectors. Seventeen evaluations were performed at monthly intervals of the incidence of rust and brown eye spot on coffee leaves. The size and distribution of the copper particles of each product with Mastersizer 2000® equipment and the pH of the syringes with digital pH meter were also evaluated. After statistical analysis, it was concluded that the association of copper and systemic fungicides was efficient in the control of brown eye spot. There is a difference between copperbased products in the control of rust and brown eye spot, the pH of the syrup increases with time in all the mixtures and losses of productivity in high levels of rust and brown eye spot reaches more than 50% less when compared to the control with fungicides. No symptoms of phytotoxicity were observed.